Connecting the Disconnected : Coping Strategies of the Financially Excluded in Bhutan - Niang, Cecile T. (Washington, DC: World Bank, 2013)
In the spring of 2012, the Royal Monetary Authority of Bhutan and the World Bank commissioned a diagnostic assessment of financial practices and strategies among urban and rural Bhutanese. The resulting survey, the Bhutan financial inclusion focus group survey, represents one of the first efforts to capture household financial management practices in the country. The assessment, undertaken at the request of a government working group led by the Royal Monetary Authority, was designed to inform Bhutan's Financial Inclusion Policy by providing information about households' use of and demand for financial services. Since the research mainly captures the perspectives of Bhutanese households, this report does not present recommendations. Instead, its findings from the field research provide qualitative evidence that has informed the financial inclusion policy by highlighting opportunities and challenges in increasing financial inclusion.